2020
DOI: 10.1186/s12968-020-00674-4
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial fibrosis in asymptomatic and symptomatic chronic severe primary mitral regurgitation and relationship to tissue characterisation and left ventricular function on cardiovascular magnetic resonance

Abstract: Background Myocardial fibrosis occurs in end-stage heart failure secondary to mitral regurgitation (MR), but it is not known whether this is present before onset of symptoms or myocardial dysfunction. This study aimed to characterise myocardial fibrosis in chronic severe primary MR on histology, compare this to tissue characterisation on cardiovascular magnetic resonance (CMR) imaging, and investigate associations with symptoms, left ventricular (LV) function, and exercise capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…93 patients attended followup investigations at 8.8 [7.4-10.6] months postoperative (Figure 1). The mean histological collagen volume fraction (CVFmean) of this patient cohort, quantified via invasive myocardial biopsy at the time of surgery, has previously been reported (5). A statistically significant correlation was present between CVFmean and ECV% (n=56, rho=0.33, P=0.015) when limiting analyses to biopsy samples containing only myocardium (without endocardial contamination).…”
Section: Baseline Characteristicsmentioning
confidence: 69%
See 2 more Smart Citations
“…93 patients attended followup investigations at 8.8 [7.4-10.6] months postoperative (Figure 1). The mean histological collagen volume fraction (CVFmean) of this patient cohort, quantified via invasive myocardial biopsy at the time of surgery, has previously been reported (5). A statistically significant correlation was present between CVFmean and ECV% (n=56, rho=0.33, P=0.015) when limiting analyses to biopsy samples containing only myocardium (without endocardial contamination).…”
Section: Baseline Characteristicsmentioning
confidence: 69%
“…It has been widely proposed that the accumulation of myocardial fibrosis is associated with subclinical LV systolic and diastolic dysfunction (18,19). This relationship is supported by animal models of volume overload induced myocardial fibrosis (20)(21)(22), and has been specifically documented in primary MR (5). Furthermore, ECV% offers incremental prognostic value compared to traditional parameters of ventricular structure and function in mutliple cardiovascular diseases (23).…”
Section: Reverse Myocardial Remodellingmentioning
confidence: 79%
See 1 more Smart Citation
“…is finding has been confirmed in another large study comprised of 120 patients with chronic primary MR, which demonstrated that fibrosis, as quantified by ECV, occurs before the onset of symptoms [33].…”
Section: Mitral Regurgitationmentioning
confidence: 62%
“…We must remember that all the landmarks illustrated are but a point of reference and not an absolute constraint, as we must take into account the person who is lying on the bed (age, morphological conformation of the chest and spine, pathologies). The presence of pathologies that change the cardiac morphology are capable of altering the cardiac position, as well as the presence of pulmonary or diaphragmatic pathologies (hernias or inspiratory or expiratory attitudes) [ 41 - 42 ]. With palpation, it is necessary to keep present the passive tensions of the pericardium and the tensions produced by the neighboring tissues in fascial connection with the pericardium; we do not have to hear the heartbeat but how the heart moves inside the pericardium and how the latter behaves inside the mediastinum.…”
Section: Reviewmentioning
confidence: 99%